One‐pot stepwise reductive amination reaction by N‐coordinate sulfonamido‐functionalized Ru(II) complexes in water. (9th October 2018) - Kayacı, Nilgün; Dayan, Serkan; Özdemir, Namık; Dayan, Osman; Kalaycıoğlu Özpozan, Nilgün
Abstract : New complexes of formula [RuCl( p ‐cymene)(L)] (7 –12 ) were prepared with [RuCl2 ( p ‐cymene)]2 and pre‐synthesized N ‐arenesulfonly‐ o ‐phenylenediamines (1 –6 ) and characterized using 1 H NMR, 13 C NMR, Fourier transform infrared and UV–visible spectroscopic techniques, and single‐crystal X‐ray diffraction analysis was performed for one complex (8 ). Complexes7 –12 were investigated in the reduced imine synthesis reaction (in the presence of HCOONa/HCOOH). The best turnover frequency values were found to be 100 h −1 for1 and 99 h −1 for6 in the transfer hydrogenative reductive amination reaction of 4‐methoxyaniline and 3, 4, 5‐trimethoxybenzaldehyde. The most important feature of this reaction is that it is an environmental friendly procedure because of being conducted in an aqueous environment. That no organic solvent is used allows one to say that this reaction represents green chemistry. Abstract : We synthesized [RuCl( p ‐cymene)(L)] complexes with N ‐arenesulfonly‐ o ‐phenylenediamine ligands and [RuCl2 ( p ‐cymene)]2 . The complexes were used as catalysts in one‐pot stepwise transfer hydrogenative reductive amination reactions of diverse aldehyde and amine derivatives in the presence of NaCOOH/HCOOH with aqueous media.